Block Estimation Technique in Spatial Statistics With Application - Jaufar Mousa Mohammed AL-bayati (Tikrit Journal of Pure Science)
This paper deals with the predictions of estimation mean of set  points (Block) at sub domain determined within domain study by one arithmetic process as if as this set of points is one point, and we used in this paper a technique called Block kriging technique, that estimator could estimate the mean of set point as (Block) in one time, moreover calculation kriging estimator variance of  block for this technique is abstract of time, hard work and the cost, and we application this idea on real data in health domain specially Cancer ills in Iraq at 2008-2009 and Has been important getting accurate results and as it deems the researchers.